Master’s Degree Program in Physical Education at the Federal University of Sergipe: profile, difficulties and perspectives - Antonio Cesar Cabral de Oliveira; Rogério Brandão Wichi; Afrânio de Andrade Bastos; Anderson Carlos Marçal; Carlos Roberto Rodrigues Santos; Ciro José Brito; Danilo Ribeiro Guerra; Emerson Pardono; José Aderval Aragão; Marco Antonio Prado Nunes; Marcos Bezerra de Almeida; Raquel Simões Mendes Netto (Revista Brasileira de Atividade Física e Saúde)
This paper presents the Physical Education Graduate Program at Sergipe Federal University (Master of Physical Education), which started in 2012. The areas of concentration are Physical Activity, Health and Sports, and under the following research directions: physical activity and health-related quality of life; determinant factors of practice and physical performance; morphofunctional adaptations of the physical exercise. The Program has been ranked by CAPES with a grade three, offering annual application for candidates graduated in physical education and related areas